Prevalence and Determinants of Female Child Marriage in Indonesia: A Secondary Data Analysis of 2012 and 2017 IDHS - Suprobo, Nina Rini; Kusuma Dewi, Nindi; Amelia, Dessy; Sulistina, Dewi Ratna; Kurniawati, Elisa Danik; Hasanah, Zumroh; Puriastuti, Alifia Candra; Gamagitta, Laras Putri; Hasanah, Winny Kirana; Movembriani, Rizqie Putri (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2026)
Background: female child marriage (FCM) remains a critical challenge in Indonesia, particularly in rural and socioeconomically disadvantaged communities. Despite legal reforms such as the revision of the Marriage Law in 2019, FCM continues to occur at alarming rates, leading to harmful health, educational, and economic consequences for young girls. Purpose: to examine the prevalence and determinants of FCM in Indonesia through a secondary data analysis of the 2012 and 2017 Indonesia Demographic and Health Surveys (IDHS). Methods: a secondary data analysis was conducted using weighted samples from the 2012 and 2017 IDHS datasets. Multivariate analysis was performed to examine associations between socio-demographic and other relevant variables with the likelihood of female children (aged 15-18 years) entering marriage. The study focused on identifying temporal trends and key risk factors contributing to early marriage among Indonesian female children. Results: this study revealed a decrease in female child marriage prevalence, from 9.15% in 2012 to 7.10% in 2017. Logistic regression analysis indicated that younger age (15–16), rural residence, and low economic status consistently increased the likelihood of early marriage. In 2012, poor STI knowledge and family planning discussions were significant predictors, while in 2017, smoking behavior and employment status became influential factors, reflecting ongoing social dynamics and structural challenges. Conclusion: female child marriage in Indonesia is strongly influenced by low education, poverty, rural residence, and limited STI knowledge. The findings highlight the need for improved education access, economic support, and tailored reproductive health programs